2017
DOI: 10.3389/fpsyg.2017.00756
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Consumption in Spanish University Alumni: Nine Years of Follow-Up

Abstract: The aim of this study was to empirically identify different profiles of Spanish university alumni, based on their alcohol use over 9 years, and to further characterize them. A cohort study was carried out between 2005 and 2015 among university students (Compostela Cohort-Spain; n2015 = 415). Alcohol consumption was measured using the Alcohol Use Disorder Identification Test (AUDIT). A two-stage cluster analysis, based on their AUDIT total scores was carried out separately for males and females. The further cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
4
14
1
Order By: Relevance
“…Living off-campus, outside of university residences and away from the parental home have also been shown to be risk factors for both alcohol abuse and alcohol dependence, although only in women. Similar results were observed in previous studies [21,40], possibly due to a stricter and more controlled home environment [58,59], mainly for young females. Moreover, the study cohorts included more females, and the lack of significance of this variable in males may be due to lower statistical power.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Living off-campus, outside of university residences and away from the parental home have also been shown to be risk factors for both alcohol abuse and alcohol dependence, although only in women. Similar results were observed in previous studies [21,40], possibly due to a stricter and more controlled home environment [58,59], mainly for young females. Moreover, the study cohorts included more females, and the lack of significance of this variable in males may be due to lower statistical power.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the rates of prevalence of alcohol abuse remained fairly constant during the three years of follow-up. Perhaps, in this case, the peak consumption has not been reached in either gender, an interpretation previously made by other authors with similar results [17,21]. It will be interesting to observe how these trends evolve in the coming years.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Alcohol is one of the most consumed and easily accessible drugs globally. In particular, certain alcohol consumption patterns such as binge drinking tend to increase among young people around the world [ 1 ]. Chronic and binge drinking was mentioned as the main determinant of the risk of alcoholic liver disease (ALD) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the BD pattern during adolescence, it is similar in 14–16 year-old adolescents and is more common among men than women in the age range of 17–18 years (Observatorio Español sobre Drogas [OED], 2016). A recent study in Spanish university alumni has revealed the existence of different typologies of alcohol users, with differences among males and females (Gómez et al, 2017). In the light of these data, it would seem crucial to consider gender differences when exploring the relationship between BD and memory in late adolescents.…”
Section: Introductionmentioning
confidence: 99%